Field scale evaluation of coagulants for filtration of Giardia cysts and other substances - McElroy, John Michael, author; Hendricks, David W., author; U.S. Environmental Protection Agency, Drinking Water Research Division, publisher (Colorado State University. Libraries, 1984)
The effect of coagulant dosage on removals of Giardia cysts, coliform bacteria, and turbidity was evaluated for two types of raw water. These removals were found for three categories of coagulant dosages: i) optimum, ii) nonoptimum, and iii) no chemicals. The "optimum" and "nonoptimum" dosages were defined with respect to turbidity removal. Large numbers of Giardia cysts and coliform bacteria passed through the rapid rate filter when chemical coagulants were not used; however, removals of greater than 99 percent were obtained by using "optimum" coagulant dosages. The two waters tested were a 5 to 10 NTU turbidity water from Horsetooth Reservoir and a 0.4 to 0.9 NTU water from fall and winter flows of the Cache La Poudre River. All testing was done using a "package" rapid rate water treatment plant, a 1.3 l/s (20 gpm) Neptune Microfloc WATER BOY. All testing was conducted using "in-line" filtration with hydraulic loading rates between 2.7 and 3.5 mm/s (4 and 5.2 gpm/ft2). Giardia cysts and coliform bacteria were injected into the raw water intake piping of the pilot plant during 31 of the 144 test runs. Of these 31 "contaminant" tests, 9 utilized raw water from the Cache La Poudre River when the turbidity was less than 1 NTU, and 22 used raw water from 5 to 10 NTU Horsetooth Reservoir. It was determined that the polymer Magnifloc 572-C in conjunction with alum will effectively coagulate Cache La Poudre River water during the winter, i.e. when raw water turbidity levels are less than 1 NTU. By using 7.0 mg/l of alum as Al2 (SO4)3 14H2O followed by 2.0 mg/1 of Magnifloc 572-C, Giardia cyst removals of 95 percent and coliform bacteria removals of 98 percent were obtained from raw water having 0.7 NTU turbidity and less than 1°C temperature. These results confirmed findings from the laboratory scale filtration experiments. Relationships between turbidity removals, coliform bacteria removals, and Giardia cyst removals were established for Horsetooth Reservoir water, and for cold, low-turbidity Cache La Poudre River water. Turbidity removal can serve as a surrogate for coliform bacteria removals and for Giardia cyst removals for these two waters. This field scale study followed guidance established by laboratory scale and bench scale filtration studies which had tested a wider range of conditions, not feasible at the field scale. Five parallel testing comparisons between the bench scale, laboratory scale, and field scale pilot plants were made in which turbidity removal vs coagulant dose was evaluated for each of the three systems. These comparisons indicated similar performances for the three systems, which helps validate the use of bench scale and laboratory scale testing to evaluate coagulants and to recommend the approximate dosage for full scale operation. This report constitutes the results of the field scale pilot plant phase of the project area on rapid rate filtration.
CER83-84JM-DWH38.
March 1984.
Report 5847-84-2.
Keywords: Giardia lamblia; Drinking water -- Purification -- United States; Water -- Purification